Relational Developmental Systems and Family Research: Considering Qualitative Applications. Issue 2 (3rd December 2018) - Bell, Nancy J.
Abstract : Relational developmental systems (RDS), a metatheory grounded in the relationism worldview, is becoming more widely accepted in developmental science. Its principles define a perspective that is relational, systemic, holistic, dynamic, and process oriented. Even though child and family development was the topic of the initial formulation of RDS nearly 40 years ago, its application in successive years has remained largely within human development. Here, I consider the applicability of this metatheory to family science. My consideration includes a summary of RDS principles; a description of RDS‐compatible qualitative research in a range of family science topic areas; a discussion of the usefulness of RDS in enhancing coherence among metatheory, methodology, theory, and methods; and conclusions about its potential fit with family science.